A variational problem for the biharmonic equation - Morozov, V.A.; Tokarev, N.M.; Lezhnev, V.G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
The problem of choosing the boundary condition on a part of the boundary is considered for a boundary value problem formulated for the biharmonic equation.